Potensi Jamur Patogen Tumbuhan sebagai Agen Pengendali Biologi Gulma Alang-alang - Bambang Nugroho; Titik Suryani; Bambang Hadisutrisno (Jurnal Perlindungan Tanaman Indonesia, 1997)
Biological control is an important component of integrated pest management, including integrated pest management on weed. One of the important biological control agents is plant pathogenic fungi. The purpose of this research is to identify potential fungi to be developed as an agent of biological control on alang-alang (Imperata cylindrica L). A survey was conducted in highland and lowland areas which were seriously infested by alang-alang to know the disease intensity and its distribution. Sample of diseased leaves were taken for identification and pathogenecity testing. Four fungal diseases - leaf blight, rust and two kinds of leaf spot that are caused by Phoma sp, Puccinia rufipes Diet and two unidentified pathogens - were found. By inoculation trials it was proven that Phoma sp. is pathogenic to alang-alang. Considering that there are potential pathogenic fungi causing several diseases on alang-alang, it is possible to develop a method of controlling the grass by using pathogenic fungi.